Sink Status and Photosynthetic Rate of the Leaflet Galls Induced by Bystracoccus mataybae (Eriococcidae) on Matayba guianensis (Sapindaceae) - Oliveira, Denis C.; Moreira, Ana Silvia F. P.; Isaias, Rosy M. S.; Martini, Vitor; Rezende, Uiara C. (Frontiers in Plant Science, 2017)
The galling insect Bystracoccus mataybae (Eriococcidae) induces green and intralaminar galls on leaflets of Matayba guianensis (Sapindaceae), and promotes a high oxidative stress in host plant tissues. This biotic stress is assumed by the histochemical detection of hydrogen peroxide, a reactive oxygen species (ROS), whose production alters gall physiology. Thus, we hypothesize that high levels of nutrients are accumulated during gall development in response to a local maintenance of photosynthesis and to the galling insect activity. Moreover, the maintenance of low levels of photosynthesis may guarantee O2 production and CO2 consumption, as well as may avoid hypoxia and hypercarbia in gall tissues. To access the photosynthesis performance, the distribution of chlorophyllous tissues and the photochemical and carboxylation rates in gall tissues were analyzed. In addition, histochemical tests for hydrogen peroxide and phenolic derivatives were performed to confirm the biotic stress, and set the possible sites where stress dissipation occurs. The contents of sugars and nitrogen were evaluated to quantify the gall sink. Currently, we assume that the homeostasis in gall tissues is ruptured by the oxidative stress promoted by the galling insect activity. Thus, to supply the demands of gall metabolism, the levels of water-soluble polysaccharides and starch increase in gall tissues. The low values of maximum quantum efficiency of PSII (Fv/Fm) indicate a low photosynthetic performance in gall tissues. In addition, the decrease of PSII operating efficiency, (F’m–F’)/F’m, and Rfd (instantaneous fluorescence decline ratio in light, to measure tissue vitality) demonstrate that the tissues of B. mataybae galls are more susceptible to damage caused by stressors than the non-galled tissues. Thus, the high oxidative stress in gall developmental sites is dissipated not only by the accumulation of phenolic derivatives in the protoplast, but also of lignins in the walls of neoformed sclereids.